An In Situ Full Charge Capacity Estimation Algorithm for Li-Ion Batteries Using Recursive Least-Squares Identification with Adaptive Forgetting Factor Tuning. (6th January 2017) - Lin, Lei; Ono, Hironori; Fukui, Masahiro; Takaba, Kiyotsugu
Abstract : This paper discuss a full charge capacity (FCC) estimation system for lithium ion batteries based on the recursive least-squares identification. The accuracy of the estimation is depended on accuracy of the state of charge (SOC) estimation. The authors have newly formulated the adaptive forgetting factor for recursive least- squares identification. As the result, the error rate of the SOC estimation has been improved. The evaluation shows the new FCC estimation system can be used for various temperature conditions.